If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40X + 20Y(200 + -1X) = 5600 40X + (200 * 20Y + -1X * 20Y) = 5600 Reorder the terms: 40X + (-20XY + 4000Y) = 5600 40X + (-20XY + 4000Y) = 5600 Solving 40X + -20XY + 4000Y = 5600 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4000Y' to each side of the equation. 40X + -20XY + 4000Y + -4000Y = 5600 + -4000Y Combine like terms: 4000Y + -4000Y = 0 40X + -20XY + 0 = 5600 + -4000Y 40X + -20XY = 5600 + -4000Y Reorder the terms: -5600 + 40X + -20XY + 4000Y = 5600 + -4000Y + -5600 + 4000Y Reorder the terms: -5600 + 40X + -20XY + 4000Y = 5600 + -5600 + -4000Y + 4000Y Combine like terms: 5600 + -5600 = 0 -5600 + 40X + -20XY + 4000Y = 0 + -4000Y + 4000Y -5600 + 40X + -20XY + 4000Y = -4000Y + 4000Y Combine like terms: -4000Y + 4000Y = 0 -5600 + 40X + -20XY + 4000Y = 0 Factor out the Greatest Common Factor (GCF), '20'. 20(-280 + 2X + -1XY + 200Y) = 0 Ignore the factor 20.Subproblem 1
Set the factor '(-280 + 2X + -1XY + 200Y)' equal to zero and attempt to solve: Simplifying -280 + 2X + -1XY + 200Y = 0 Solving -280 + 2X + -1XY + 200Y = 0 Move all terms containing X to the left, all other terms to the right. Add '280' to each side of the equation. -280 + 2X + -1XY + 280 + 200Y = 0 + 280 Reorder the terms: -280 + 280 + 2X + -1XY + 200Y = 0 + 280 Combine like terms: -280 + 280 = 0 0 + 2X + -1XY + 200Y = 0 + 280 2X + -1XY + 200Y = 0 + 280 Combine like terms: 0 + 280 = 280 2X + -1XY + 200Y = 280 Add '-200Y' to each side of the equation. 2X + -1XY + 200Y + -200Y = 280 + -200Y Combine like terms: 200Y + -200Y = 0 2X + -1XY + 0 = 280 + -200Y 2X + -1XY = 280 + -200Y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| Dy/dx=senx5x | | 13x+3y=50 | | y^2+3y+8=-2y+4 | | 5=4a+7a-3b | | (2x+6)+(5x-12)=99 | | x-1/3-x-1/2=5/4 | | (5x+1)(x-3)=(x-5)(5x-2)+2 | | 3(k-1)=k+6 | | y=50x+4 | | 4-5y=7-2(y-6) | | p=18-(2-3p) | | 49s-26=107 | | 6x-(5+2x)+5=x | | 5(p-1)=p+5 | | 5/8÷25/16= | | 2-4x=3x-5 | | e(2x+1)+7e(x)-15=0 | | 7x=31412+312 | | 36t^2+128t^3=9 | | -36t^2+128t^3=9 | | 5+3=x-3x-2x | | -72*t^2+256*t^3=18 | | x^10=1.55 | | x^10=15 | | 140x+x=180 | | -4x^3=-4x | | -2+a-b+1=0 | | 1+a+2b+4=0 | | x+4*3-4=65 | | (x-9)(x-12)=0 | | a=bx+cx^3 | | 7x-2y+4=o |